2021
DOI: 10.1088/1757-899x/1010/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of anthocyanin pigment from hibiscus sabdariffa l. by ultrasonic-assisted extraction

Abstract: Roselle flower contains various active compounds including organic acid, hydroxycitric acid, hibiscus acid, anthocyanin, flavonoids and polysaccharides The anthocyanin compounds in rosella flowers are the most important pigment of vascular plants, harmless and that make it interesting is a soluble pigment in water media Anthocyanin extract is one of the most successful natural sensitizers for solar cells, because this organic dye produces a high yield of photons to current conversion and is easy to obtain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
6
0
4
Order By: Relevance
“…Pinela et al (2017) also demonstrated that ultrasound‐assisted extraction has the advantage of recovering anthocyanins from Hibiscus sabdariffa calyces. Yuniati et al (2021) found that ultrasound at a frequency of 24 kHz lasting 5 min showed a rich source of anthocyanins, however, the use of high temperatures and longer extractions could damage the pigments in cells. Similar studies also observed that ultrasonic‐assisted extraction was more effective for extraction of anthocyanins from butterfly pea than conventional extraction (Syafaa' tullah et al, 2020).…”
Section: Extraction Methodologies Of Anthocyanins In Edible Flowersmentioning
confidence: 99%
“…Pinela et al (2017) also demonstrated that ultrasound‐assisted extraction has the advantage of recovering anthocyanins from Hibiscus sabdariffa calyces. Yuniati et al (2021) found that ultrasound at a frequency of 24 kHz lasting 5 min showed a rich source of anthocyanins, however, the use of high temperatures and longer extractions could damage the pigments in cells. Similar studies also observed that ultrasonic‐assisted extraction was more effective for extraction of anthocyanins from butterfly pea than conventional extraction (Syafaa' tullah et al, 2020).…”
Section: Extraction Methodologies Of Anthocyanins In Edible Flowersmentioning
confidence: 99%
“…Antosianin tersusun atas sebuah aglikon (antosianidin) yang teresterifikasi terhadap gugus glikon gula. Senyawa ini memiliki beberapa bentuk antosianidin yang berbeda, mulai dari sianidin, pelargonidin, malvidin, petunidin, peonidin, dan delfinidin [6]. Dengan bentuk yang berbeda ini, senyawa antosianin dapat diwujudkan dalam rentang variasi kenampakan warna biru, merah, hingga ungu, yang mana hal ini menjadi kekhasan tersendiri dari senyawa antosianin [7].…”
Section: Pendahuluanunclassified
“…attempted to study the extraction process of telang flower petals to obtain anthocyanin extract and determine the factors that influence the extraction process using the Ultrasound Assisted Extraction method, so that it can finally be used as a beverage product. From this research, the optimum achievement for dye extraction from butterfly pea petals was at conditions of F/S 0.02 g/ml, extraction temperature of 60°C, and extraction time of 90 minutes, with anthocyanin concentration in the drink obtained at 19.57 mg/L.…”
mentioning
confidence: 93%
“…Penelitian awal terkait metode ekstraksi SFME pada bunga mawar sangat diperlukan untuk mengetahui kondisi optimum ekstraksi untuk mendapatkan zat ekstrak dengan persentase yield setinggi-tingginya [11,12]. Selain itu, penelitian ini juga diperlukan untuk mengetahui kandungan senyawa yang ada pada minyak atsiri yang berhasil diekstrak dengan metode green chemistry.…”
Section: Pendahuluanunclassified